Implementasi Nilai Toleransi Bagi Mahasiswa Guna Mencapai Perdamaian dalam Bermasyarakat - Nasution, Akmal Ludin; Fitri, Awalia Nur; Yasmin, Firly Alvia (Badan Penerbit STIEPARI Press, 2025)
This research provides an in-depth examination of the dynamics of religious tolerance in Indonesia in the face of challenges from modernity, globalization, and digitalization. As a multicultural nation, Indonesia is rich with a diversity of religions, cultures, and ethnicities, yet it is also vulnerable to the risk of conflict if tolerance is not properly maintained. Therefore, this study aims to analyze the various efforts and strategies required to strengthen religious tolerance as the primary foundation for national unity. The method used is library research with a descriptive qualitative approach, which involves a comprehensive analysis of various literature, journals, and official documents related to this topic. The research findings indicate that tolerance is not merely a normative concept but a practical necessity that has been manifested throughout the history and social practices of Indonesian society. The success of the City of Singkawang as a model tolerant city serves as tangible evidence that harmony can be realized through interaction and shared consciousness. However, the effort to maintain this tolerance faces various complex challenges, such as radicalism, political polarization, and the misuse of social media, which triggers hate speech, hoaxes, and exclusivism. Religious tolerance is a crucial social capital that must be collaboratively strengthened by all elements of the nation, including the public, religious leaders, and the government. To overcome these challenges, this study recommends an integrated strategy that includes inclusive education from an early age to instill values of mutual respect, as well as regular interfaith dialogue to dismantle stereotypes. Furthermore, the government needs to formulate policies that support diversity, and the media must be optimally utilized to disseminate positive narratives. These efforts, combined with the strengthening of daily social interactions, will be effective in building empathy and mutual trust, making tolerance a solid pillar for creating a peaceful, inclusive, and harmonious national life amid the dynamics of modernity and digitalization.